Generalized Green's functions for higher order boundary value matrix differential systems - R. J. Villanueva; L. Jodar (International Journal of Mathematics and Mathematical Sciences)
In this paper, a Green's matrix function for higher order two point boundary value differential matrix problems is constructed. By using the concept of rectangular co-solution of certain algebraic matrix equation associated to the problem, an existence condition as well as an explicit closed form expression for the solution of possibly not well-posed boundary value problems is given avoiding the increase of the problem dimension.